2021
DOI: 10.1088/2053-1591/abe6db
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acrylonitrile styrene acrylate on mechanical, thermal and three-body abrasion behaviors of eucalyptus fiber reinforced polyvinyl chloride composite

Abstract: The effect of different content (0–20 wt%) Acrylonitrile-styrene-acrylic (ASA) on mechanical, thermal and three-body wear behaviors of eucalyptus fiber/polyvinyl chloride (EF/PVC) composites were studied in this research. The results show that the mechanical properties of the composites such as impact strength, tensile strength, flexural strength and flexural modulus increased with increasing ASA content lower than 15 wt%. The addition of 15 wt% and 20 wt% ASA can improve thermal stability of the EF/PVC compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the second stage, the weight loss temperature was 380 to 510 ℃, and the weight loss rate was approximately 15%, which was a small part of weight loss. This stage mainly includes the continued pyrolysis of lignin and the nuclear structure (PBA) in ASA, the complete volatilization of residual HCl in PVC, and the fracture thermal decomposition of carbon chain skeleton in PVC molecular chain (Zhang et al 2021). When ASA content was 10 wt%, the second stage weight loss starting temperature of eucalyptus/PVC composite was the highest at 415.8 ℃, which was considerably higher than that of the composite without ASA.…”
Section: Ft-ir Comparison Of Asa Modified Eucalyptus/pvc Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second stage, the weight loss temperature was 380 to 510 ℃, and the weight loss rate was approximately 15%, which was a small part of weight loss. This stage mainly includes the continued pyrolysis of lignin and the nuclear structure (PBA) in ASA, the complete volatilization of residual HCl in PVC, and the fracture thermal decomposition of carbon chain skeleton in PVC molecular chain (Zhang et al 2021). When ASA content was 10 wt%, the second stage weight loss starting temperature of eucalyptus/PVC composite was the highest at 415.8 ℃, which was considerably higher than that of the composite without ASA.…”
Section: Ft-ir Comparison Of Asa Modified Eucalyptus/pvc Compositesmentioning
confidence: 99%
“…As a kind of high quality, fast growing, and high yielding tree species, eucalyptus has become one of the most important afforestation trees in the global plantation industry, which solves the problem of slow growth rate effectively and unsustainable development of primary forests (Wang et al 2016). Zhang et al (2021) studied the effects of different contents of ASA on the mechanical properties, thermal properties, and three-body wear properties of eucalyptus fiber/polyvinyl chloride (EF/PVC) composites. The results showed that the addition of ASA can improve the mechanical properties, thermal stability, and three-body wear resistance of EF/PVC/ASA composites.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al [22] investigated that ASA particles with 60 wt% PBA rubber core were the most suitable impact modifier for SAN resin, since it exhibited a good balance between toughness and rigidity. Furthermore, the influence of ASA particle addition amount, degree of crosslinking, and many other factors were fully discussed in others' work [23][24][25][26]. However, the effect of the microstructure of ASA particles on the toughening effect has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%